UNSUR SUARA SEBAGAI BRAND IMAGE DALAM PERLINDUNGAN MEREK - Saputra, Guruh Eka ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this study is to answer the problem about how the sound element can be registered as a trademark, and arrangement in the Trademark Act No. 15 of 2001 and how the comparative with the another states. The method of this research was conducted by Judicial Normative approaches are, that is a research explaining the legal protection of brands, particularly concerning the legal protection of sound elements according to the legal provisions Trademark Act No. 15 of 2001, or by the rules and other legal rules that apply with purposive sampling technique. The research was conducted on the Office of Directorate General of Intellectual Property of Tangerang with the research subjects is Head of Legal Services Directorate Marks. The data has been obtained by the literature research and the observed data will be systematically note and will be analyzed in qualitative. The results of this research indicate that not all the sound element can be registered as a trademark sound, only sound which unique, distinctiveness and functional specificity that could registered as a trademark. It also, the sound element which will be registered as a trademark must be represented in graphical form and the notation tone that is consistent. Trademark Act No. 15 of 2001 not arrangement according explicitaly in the article of legal provision. Soundmark in the state with advanced industry like USA, Australia and England has been regulate in differents way by legal provision. From the results of research related to the sound element in trademark protection, there is a few advice which may be provided by the author, in the practice of sound trademark registration, Trademark Office need to procure the provision of facilities digital technologies which supports the registration of marks to store the sound registered as a trademark in a data base which is accessible any time and there is a need more specific legal rules which regulate the requirement could whether or not the sounds registered as a trademark and its juridical restrictions to prevent the multiple interpretations of the soundmark registration.